Antioxidant and prebiotic activity of (1→3)-β-D-glucan obtained from Rhodotorula mucilaginosa - Lobo , Patrícia Teixeira Damasceno; Teshima , Elisa; Assis , Sandra Aparecida de (Seven Editora, 2023)
The β-Glucans has high biotechnological potential application in several industrial sectors. Then, the antioxidant and prebiotic activity of (1→3)-β-D-glucan obtained from the cell wall of R. Mucilaginosa yeast was evaluated. The strains tested Bifidobacterium Lactis and Bifidobacterium longum showed a comparable result with the commercially inulin. The digestibility of glucan was investigated in vitro by exposing them to artificial human gastric juice. The results show that not occurred hydrolysis of (1→3)-β-D-glucan under the studied conditions and the glucan remain undigested in 100%. Antioxidant capacity was evaluated by ABTS, DPPH and total antioxidant capacity test. The results of DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity showed a maximum inhibition percentage of 51.00% and the test of total antioxidant capacity showed that 10 mg/mL of (1→3)-β-D-glucan shows the same result as the use of the 222.27 ± 4.3 µg/mL ascorbic acid. The obtained results show that the (1→3)-β-D-glucan extracted from the cell wall of R. mucilaginosa has the potential to be explored as a food ingredient with functional capacity. DOI:https://doi.org/10.56238/uniknowindevolp-053